UNBROKEN SPIRIT: A CRITICAL ANALYSIS OF NADIA MURAD’S THE LAST GIRL AND ITS PORTRAYAL OF TRAUMA AND RESILIENCE - Philip, Bindu Ann; Sreeja G. (International Journal of Research -GRANTHAALAYAH, 2025)
The paper engages trauma as an unrepresented phenomenon in the classic model; hence, it tries to illustrate the pervasive impact it exerts on literary criticism and cultural discourse. Grounding on Cathy Caruth’s notion of trauma as an unreceived experience that surfaces and haunts the survivor, the paper identifies intricacies surrounding the dynamic relations of violence, memory, and representation. Through the eyes of Nadia Murad’s memoir, The Last Girl: My Story of Captivity and My Fight Against the Islamic State, the conversation digs into the Yazidi genocide and Murad’s personal testimony as a survivor of sexual slavery and forced conversion under ISIS. The memoir is analyzed both as an individual narrative of survival and as a broader commentary on the human condition amidst collective suffering. This is further complemented by the entwinement of personal and communal trauma, making it easier to understand the interplay of victim, executioner, and see to approach psychological and sociocultural implications of violence. The research also focuses on how storytelling could become a vital function of keeping memory, creating resilience, and demanding justice after an atrocity.